Rancangan Sistem Akuntansi Penerimaan Kas, Pengeluaran Kas dan Penggajian Pada PT Lanefa Karya Persada - Zalida Afni; Anda Dwi Haryadi; Salma D (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
This study aims to determine and provide recommendations for improving the existing accounting system at the company PT Lanefa Karya Persada. PT Lanefa Karya Persada is a company engaged in housing and real estate construction. Based on the data that the authors get, there are still weaknesses in the accounting system for cash receipts, cash disbursements and payroll, both in terms of procedures, documents and accounting records. This study recommends that companies further maximise cash receipt and expenditure procedures for housing. In addition, the authors advise companies to complete or improve accounting documents and records in accordance with the principles of document design.